FEATURES OF INNOVATION IN HEALTH CARE (Journal of Economic Research & Business Administration, 2018)
The article considers the relevance of the development and introduction of innovations in the medical industry. The authors cite the classification of the main types of innovations, note the need for their development. The work reveals the specifics of the innovation cycle in the medical industry. The changes in the application of innovative technologies in the healthcare sphere are demonstrated, examples of successfully implemented innovative technologies in medical practice are given, which contributed to the increase of innovations in the medical industry as a whole.The main goal of this work is to analyze the need for close interaction between the healthcare sector and medical science in order to introduce innovative scientific achievements into medical practice. The need to train qualified personnel capable of successfully implementing scientific innovations was also noted. The authors also highlight the main problems facing the introduction of innovations in the healthcare sector, highlighting issues on innovative provision of health care. The issues of state guarantees and legislative protection of domestic scientific developments are also considered as a basis for further development of innovations in the industry.